HIPERTENSI EMERGENSI DI INTENSIVE CARE UNIT (ICU) RUMAH SAKIT UMUM DAERAH (RSUD) TUGUREJO SEMARANG - Setyoningrum Pujiastuti; Fef Rukminingsih (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2022)
A sudden increase in blood pressure reaching> 180/120 mmHg accompanied by involvement of organ damage is called hypertensive emergencies. Nationwide Emergency Department recorded visits of hypertensive emergency cases as much as 3309 million in 2006 and 6178 million in 2013. The Hospital data information system (SIMRS) in Tugurejo Regional Hospital Semarang in 2017 found that the number of patients diagnosed with hypertension reached 1,125 patients. The aim of this study was to evaluate the use of antihypertension in hypertensive emergency patients in the Intensive Care Unit (ICU) of Tugurejo Hospital Semarang in the period January - December 2018. This study is a descriptive observational study using retrospective data. Data retrieval was done by looking at the medical record data of patients with hypertensive emergencies who received hypertension therapy in the ICU Tugurejo Hospital in the period January - December 2018. Data were analyzed based on patient characteristics, antihypertensive use patterns and evaluation of antihypertensive use. The number of patients who fulfilled the inclusion and exclusion criteria were 58 patients. The results of this study indicate that the suitability of antihypertensive use in decreasing systolic blood pressure at 1 hour, 2 – 6 hours, 24 – 48 hours in a row is 81.03%; 24.14%; 20.93%. Whereas for a decrease in diastolic blood pressure at 1 hour, 2 – 6 hours, 24 – 48 hours respectively 77.59%; 43.10%; 74.42% according to the ACC / AHA guidelines (2018).